Finite element analysis of the vertical roller mill based on ANSYS Workbench. (26th November 2019) - Wei, Weihua; Zhu, Hongwei; Li, Yuantong; Jin, Peng
By using of element analysis software ANSYS Workbench, the static analysis of lower rocker arm and column, and the modal analysis of column are carried out. The three-dimensional models of lower rocker arm and column were imported into the ANSYS Workbench for meshing. The loads and constraints were imposed on the meshed model to solve for the stress and deformation. The contour plots of stress and the total deformation of the lower rocker arm and column indicate that the structure meets the design requirements in strength and stiffness, which verifies the reliability of the structure. Through the modal analysis of column under free and constrained states, the first eight natural frequencies and vibration modals under free and constrained states are obtained, which can intuitively reflect the dynamic characteristics of the column itself, help to avoid structural resonances in engineering applications, and provide a theoretical basis for the optimisation design and fault detection of the column.